Usulan Penjadwalan Penggantian dan Pemeriksaan Komponen Kritis Mesin Feeder dan Fanblower (Studi Kasus di PT. Petnesia Resindo) - Ivanasari Latib; Carla Olyvia Doaly (JURNAL TEKNIK INDUSTRI, 2018)
Many companies do not pay attention to machine maintenance. One of them is PT Petnesia Resindo. The company that have been engaged in platic is still implementing a breakdown maintenance. This proved to disturb the production process. Sothis research is interested in trying to implement preventive maintenance against the proposed machine company, Research begins with the determination of critical machines based on the OEE level. Both engines are feeder and fanblower engine is including a critical engine. The critical components based on the rules " 80-20 "pareto diagram are tapper roll bearing, thrust ball bearing,timing belt,and disc pack coupling . After the analysis of distribution test, it will get the replacement interval and checking interval replacement tapper roll bearings is 1300 hours, for thrust ball bearing component is 1900 hours, for timing belt component is 3220 hours, and for disc pack components is 2080 hours As for the inspection interval of tapper roll bearing component is 1034 hours, for thrust ball bearing component is 1179 hours, for timing belt component is 2545 hours, and disc pack component is 1280 hours. After implementing preventive maintenance it is expected cost savings and slowing down the level of reliability. The cost savings of tapper roll bearing component is around 71%, for thrust ball bearing component is 76%, for timing belt component is 61%, and disc pack component is 59%.